Facilitators of HCV treatment adherence among people who inject drugs: a systematic qualitative review and implications for scale up of direct acting antivirals. (December 2016) - Rich, Zachary; Chu, Carissa; Mao, Jessica; Zhou, Kali; Cai, Weiping; Ma, Qingyan; Volberding, Paul; Tucker, Joseph
Abstract Background While the public health benefits of new HCV treatments depend on treatment adherence, particularly among people who inject drugs (PWID), several social and medical factors can jeopardize treatment adherence. The aim of this study is to examine the qualitative literature on facilitators to HCV treatment adherence among PWID. Methods We searched six databases to identify qualitative research studies on HCV treatment adherence facilitators among PWID. Two reviewers independently extracted and analyzed data using PRISMA guidelines and the CASP tool to evaluate study quality. Results From ten studies representing data from 525 participants, three major themes emerged across studies: logistical facilitators within health systems enhanced HCV treatment adherence, positive social interactions between PWID and staff provided positive feedback during treatment, and HCV treatment may complicate the addiction recovery process. Conclusions Although PWID face several barriers to adherence, we identified treatment adherence facilitators that could be incorporated into clinical practice.